Lynx1 and the family of endogenous mammalian neurotoxin-like proteins and their roles in modulating nAChR function - Talulla B. Palumbo; Julie.M. Miwa (Elsevier, 2023)
The promise of nicotinic receptors as a therapeutic target has yet to be fully realized, despite solid data supporting their involvement in neurological and neuropsychiatric diseases. The reasons for this are likely complex and manifold, having to do with the widespread action of the cholinergic system and the biophysical mechanism of action of nicotinic receptors leading to fast desensitization and down-regulation. Conventional drug development strategies tend to focus on receptor subtype-specific action of candidate therapeutics, although the broad agonist, nicotine, is being explored in the clinic. The potential negative effects of nicotine make the search for alternate strategies warranted. Prototoxins are a promising yet little-explored avenue of nicotinic receptor drug development. Nicotinic receptors in the brain belong to a complex of proteins, including those that bind to the extracellular face of the receptor, as well as chaperones that bind the intracellular domain, etc. Lynx prototoxins have allosteric modularity effects on receptor function and number and have been implicated in complex in vivo processes such as neuroplasticity, learning, and memory. Their mechanism of action and binding specificity on sets of nAChR subtypes present intriguing possibilities for more efficacious and nuanced therapeutic targeting than nicotinic receptor subtypes alone. An allosteric drug may restrict its actions to physiologically relevant time points, which tend to be correlated with salient events which would be encoded into long-term memory storage. Rather than blanketing the brain with a steady and prolonged elevation of agonist, an allosteric nAChR compound could avoid side effects and loss of efficacy over time. This review details the potential strengths and challenges of prototoxin proteins as therapeutic targets, and some of the utility of such therapeutics based on the emerging understanding of cholinergic signaling in a growing number of complex neural processes.